Self-organized etching technique for fabricating a quasiregular array of MnAs nanoislands - Takagaki, Y; Wiebicke, E; Hesjedal, T; Kostial, H; Herrmann, C; Daweritz, L; Ploog, K (2003)
Self organized etching techniques for fabricating a quasiregular array of MnAs nanoislands were discussed. The strain balance in the MnAs layer grown on GaAs substrates collapsed when the heterostructure was immersed in a wet-chemical etch solution and regular row of cracks and submicron-wide strips were carved from it. It was also shown that MnAs islands could serve as a nearly ideal etch mask to create GaAs columns by dry etching.